Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2014)
The efficient and practical formal syntheses of both enantiomers of cis 3-hydroxypipecolic acid were accomplished from cis aziridine-2-carboxylate as the common synthetic precursor. The key steps involved are stereo and regioselective aziridine ring opening, reductive cyclization and selective N-debenzylation over O-debenzylation reactions. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 3-Hydroxypipecolic acid; Aziridine ring opening; Aziridine-2-carboxylate; Piperidine alkaloids; Selective debenzylation

Short enantioselective total synthesis of (R)- and (S)-pipecolic acid - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Kalbhor, Dinesh B. (Tetrahedron-Asymmetry, 2014)
A convenient and practical total synthesis of (R)- and (S)-pipecolic acid has been achieved by utilizing chiral cis-aziridine-2-carboxylate as the common synthetic precursor. The synthesis involves regioselective reductive cleavage of the aziridine ring and Wittig olefination as key reactions. (C) 2014 Elsevier Ltd. All rights reserved.

Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid (vol 55, pg 6423, 2014) - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2020)

Application of allylic amine formation from aziridine-2-ol under appel reaction condition: synthesis of N-(tert-butoxycarbonyl)-D-vinyl glycine methyl ester - Chavan, Subhash P.; Kawale, Sanket A.; Patil, Niteen B.; Kalbhor, Dinesh B. (Tetrahedron Letters, 2021)
PPh3/I-2/imidazolde mediated allyl amine formation from aziridine-2-alcohol was explored for the synthesis of N-(tert-butoxycarbonyl)-D-vinyl glycine methyl ester. (C) 2021 Published by Elsevier Ltd.
Keywords: Allyl amine; Aziridine-2-alcohol; Aziridinium ion; Birch reaction; Ring opening

Divergent approach to the synthesis of (-)-balanol heterocycle and cis-3-hydroxypipecolic acid based on chiral 2-aminoalkanol equivalent - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron, 2021)
Enantioselective synthesis of the hexahydroazepine core of (-)-balanol and formal synthesis of cis-3hydroxypipecolic acid from a common intermediate have been accomplished by a divergent path. The common intermediate was accessed from a favorably protected enantiomerically pure 2-amino-1,3,4-butanetriol (ABT) equivalent via oxidation and Wittig olefination. The synthesis of (-)-balanol heterocycle featured tandem reduction/acetal-deprotection/gamma-lactonization reaction and a one-pot azide reduction followed by seven membered aza-heterocycle formation while the route to cis-3-hydroxypipecolic acid highlighted the base induced piperidine ring formation and regioselective benzylidine-acetal cleavage. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Amino-alcohol; desymmetrization; Hexahydroazepine; Piperidine alkaloids; Protein kinase

Rapid synthesis of the epi-biotin sulfone via tandem S,N-carbonyl migration/aza-michael/spirocyclization and haller-bauer reaction - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (ACS Omega, 2022)
A synthesis of 2-epi-biotin sulfone was accomplished from commercially available L-cysteine. The synthesis features an unprecedented tandem S,N-carbonyl migration/aza-Michael/spirocyclization reaction from an L-cysteine-derived enone with aq. ammonia, in which three new sigma bonds and two rings are formed. In addition, the synthesis includes a highly diastereoselective late-stage Haller-Bauer reaction of sulfone for direct introduction of the carbon side chain.

Rapid bioinspired N-acyliminium ion strategy for the ABC core of the stemona alkaloids - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Asian Journal of Organic Chemistry, 2023)
A concise and highly diastereoselective bioinspired key cationic cyclization strategy for the asymmetric synthesis of the tricyclic core of the (-)-stemoamide, together with 8,9-bis-epi-stemoamide has been described. The key N-acyliminium ion precursors were accessed from L-tartaric acid and L-malic acid respectively. The use of ethyl acetoacetate derived bifunctional allylidenetriphenylphosphorane reagent in the early stage of the synthetic strategy is advantageous for the rapid construction of highly functionalized key pyrrolo[1,2-& alpha;]azepine frameworks.
Keywords: alkaloids; Biomimetic synthesis; Claisen rearrangement; cyclization; Regioselectivity